Salmonella—how a metabolic generalist adopts an intracellular lifestyle during infection - Dandekar, Thomas; Fieselmann, Astrid; Fischer, Eva; Popp, Jasmin; Hensel, Michael; Noster, Janina (Frontiers in Cellular and Infection Microbiology, 2015)
The human-pathogenic bacterium Salmonella enterica adjusts and adapts to different environments while attempting colonization. In the course of infection nutrient availabilities change drastically. New techniques, ‘-omics’ data and subsequent integration by systems biology improve our understanding of these changes. We review changes in metabolism focusing on amino acid and carbohydrate metabolism. Furthermore, the adaptation process is associated with the activation of genes of the Salmonella pathogenicity islands (SPIs). Anti-infective strategies have to take these insights into account and include metabolic and other strategies. Salmonella infections will remain a challenge for infection biology.